The High-Resolution Ultrasonography and Electrophysiological Studies in Nerve Decompression for Ulnar Nerve Entrapment at the Elbow - Zhong, Wenxiang; Zhang, Wenchuan; Zheng, Xuesheng; Li, Shiting; Shi, Jun (Journal of Reconstructive Microsurgery, 2012)
Objective To discuss a combination of high-resolution ultrasound and electrophysiological examination in diagnosis and evaluation of ulnar nerve entrapment at the elbow.Method We retrospectively reviewed 20 healthy volunteers and 278 patients of ulnar nerve entrapment divided into three groups by McGowan grade, and we treated patients with subcutaneous or modified submuscular ulnar nerve transposition randomly. All the patients were followed for 2 years. The diagnosis and effects were confirmed by preoperative or postoperative cross-sectional area (CSA), motor conduction velocity (MCV), sensory conduction velocity, and nerve action potential (NAP).Results Healthy volunteers and grade I patients had significant differences in CSA, MCV, and NAP; grade I, II, and III patients had significant differences in CSA, MCV, and NAP; all patients had significant differences in CSA, MCV, and NAP before and after operations.Conclusion High-resolution ultrasound and electrophysiological examination can be used in diagnosis and evaluation of operations of ulnar nerve entrapment at the elbow.
Keywords: ulnar nerve entrapment (cubital tunnel syndrome); high-resolution ultrasound; NCV; NAP; electrophysiological examination